2018
DOI: 10.3390/nu10101392
|View full text |Cite
|
Sign up to set email alerts
|

Branched-Chain Amino Acid Database Integrated in MEDIPAD Software as a Tool for Nutritional Investigation of Mediterranean Populations

Abstract: Branched-chained amino acids (BCAA) are essential dietary components for humans and can act as potential biomarkers for diabetes development. To efficiently estimate dietary intake, we developed a BCAA database for 1331 food items found in the French Centre d’Information sur la Qualité des Aliments (CIQUAL) food table by compiling BCAA content from international tables, published measurements, or by food similarity as well as by calculating 267 items from Greek, Turkish, Romanian, and Moroccan mixed dishes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…Branched-chain amino acids (BCAAs) are leucine, isoleucine, and valine amino acids metabolized primarily within the skeletal muscle [ 1 ]. BCAAs are found in different amounts in red meat and poultry (36.3%), milk and dairy products (16.7%), cheese (9.8%), bread, pasta, and cereals (17.3%), and legumes (4.8%) [ 2 ]. In addition, BCAA supplements are commercially available in different dosages (from 600 mg to 8000 mg per serving) and various ratios of leucine, isoleucine, and valine amino acids (usually in a 2:1:1 ratio) in sports markets [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Branched-chain amino acids (BCAAs) are leucine, isoleucine, and valine amino acids metabolized primarily within the skeletal muscle [ 1 ]. BCAAs are found in different amounts in red meat and poultry (36.3%), milk and dairy products (16.7%), cheese (9.8%), bread, pasta, and cereals (17.3%), and legumes (4.8%) [ 2 ]. In addition, BCAA supplements are commercially available in different dosages (from 600 mg to 8000 mg per serving) and various ratios of leucine, isoleucine, and valine amino acids (usually in a 2:1:1 ratio) in sports markets [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Controls were recruited during annual check-ups, and for the French subjects, additional controls were included from the GEHA (Genetics of Health Aging) project [ 32 ]. Patient’s data were recorded through a secure portal ( https://xz.univ-montp1.fr ) using the MEDIPAD software and were stored in Medigene, Anthropological & Genetic DataBase (MAGDB) [ 14 ]. For replication, we used an extended sample (n = 832) from Southern Europe ( Turkey , Italy , Greece and Spain ).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies indicate that reduction of BCAA intake in a Western diet was sufficient to improve metabolic health, weight reduction, insulin sensitivity and to transiently induce secretion of the fibroblast growth factor 21 (FGF-21) [ 12 , 13 ]. Dietary intake of BCAA was also correlated with obesity in Mediterranean populations and with IR or T2D [ 14 16 ]. Other emerging data indicated that not only BCAA concentration per se but concomitant altered oxidative metabolism, particularly involving the muscle tissue, would be involved in IR [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this population it was observed a lower incidence of COVID-19 in children and females compared to adults and males. While Iceland may represent an excellent model to understand genetics of COVID-19, the Mediterranean populations are by contrast more complicated since Mediterranean borders were places of admixed populations for millennia, including the admixture with North African populations (27)(28)(29). It is worth saying that analysis of genetic data triggering the MetS and its components from the MEDIGENE program ((https:// cordis.europa.eu/result/rcn/195753_fr.html) in the Mediterranean area would be of crucial importance.…”
Section: Host Geneticsmentioning
confidence: 99%